THE ROLE OF MOTIVATION IN LEARNING ENGLISH AS A FOREIGN LANGUAGE (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
Motivation plays a crucial role in the process of learning English as a Foreign Language (EFL). It is widely recognized as one of the most significant psychological factors influencing language acquisition. This paper aims to examine the impact of different types of motivation - intrinsic and extrinsic - on EFL learners’ performance, persistence, and overall achievement.